Pengaruh Pembelajaran Aktif Berbantuan Media Wayang Kertas Terhadap Ketrampilan Berbicara Siswa - Anisa, Fitri (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the active learning model assisted by paper puppet media on the speaking skills of third grade students at Surodadi 3 Candimulyo State Elementary School, Magelang Regency. This study uses a pre-experimental design method of the type of one group pretest-posttest. The population in this study were all third grade students at SDN Surodadi 3 Candimulyo, totaling 17 students. The research subjects were selected using a saturated sampling technique. The method of data collection is done by using a performance assessment. The validity test of the performance assessment instrument was carried out using expert validity. The analysis prerequisite test consists of a normality test and a hypothesis test. Data analysis used parametric statistical techniques, namely the paired sample T-Test test with the help of the SPSS version 22 for windows program. The results of data analysis using the paired Sample T-test showed a significance value (2-tailed) 0.000 <0.05. Based on the results of data analysis, the average pretest score was 60 while the posttest score was 74. These results showed an increase in the pretest- posttest score of 23%. The results of the study concluded that the use of active learning models assisted by paper puppet media had an effect on students’ speaking skills.